Mobile ad hoc robots and wireless robotic systems : design and implelmentation - Aquino Santos, Raul, 1965-; Lengerke, Omar, 1975-, editor; Block, Arthur Edwards, editor (Hershey, PA : Information Science Reference, 2013)
Includes bibliographical references and index